Concept as a Basic Category of Linguoculturology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Concepts, as key words of culture, reflect the cultural and national ideas of an ethnic group about the world. They are represented in consciousness as mental entities, but have a name in language and are explicated using the linguistic means of a particular language. The concept of “concept” in linguoculturology is considered as a synonym for the concept of “category of culture”, since, like the category of culture, the concept is studied as a unit of the mental picture of the world.